Prevalence and predictors of co‐occurring diabetes and hypertension in community‐dwelling older adults. Issue 9 (10th August 2018) - Sims, Omar T.; Oh, Hyejung; Noh, Hyunjin; Melton, Pamela A.; Sheffield, Samantha; Ingram, Kacey; Sawyer, Patricia
Abstract : Aim: The objectives of the present study were to estimate the prevalence of co‐occurring diabetes and hypertension among older adults, examine predictors of co‐occurring diabetes and hypertension, and ascertain whether predictors varied by race. Methods: A retrospective analysis was carried out using a statewide survey of Alabama community‐dwelling older adults ( n  = 1204). Measures of central tendency and frequency distributions were used for univariate analysis. Logistic regression was used to predict co‐occurring diabetes and hypertension. Results: The prevalence of co‐occurring diabetes and hypertension among older adults was 17%. African American race (OR 2.28, 95% CI 1.596–3.255), body mass index ≥30 (OR 2.45, 95% CI 1.732–3.463), heart disease (OR 1.93, 95% CI 1.355–2.756) and eye disease (OR 1.44, 95% CI 1.018–2.024) were associated positively with co‐occurring diabetes and hypertension. Conclusions: The prevalence of co‐occurring diabetes and hypertension among older adults was alarmingly high. The notable difference in the likelihood of co‐occurring diabetes and hypertension is representative of a racial health disparity that largely disfavors African American older adults. Findings from the present study highlight a need for identification of older adults who have and who are at risk of co‐occurring diabetes and hypertension in the general population and in clinical settings, and the development and implementation of suitable interventions, particularly targeting older African American adults.Geriatr Gerontol Int 2018; 18: 1356–1360 .